1993
DOI: 10.1002/tera.1420480107
|View full text |Cite
|
Sign up to set email alerts
|

Developmental toxicity evaluation of diethyl and dimethyl phthalate in rats

Abstract: Diethyl phthalate (DEP) and dimethyl phthalate (DMP), phthalic acid ester (PAE) plasticizers, were evaluated for developmental toxicity because of reports in the literature that some PAE were embryotoxic and teratogenic. A previous study (Singh et al., '72) suggested that an increased incidence of skeletal defects in rats might result from gestational exposure to DEP (0.6-1.9 g/kg) or DMP (0.4-1.3 g/kg), ip, on gestational days (gd) 5, 10, and 15. In the current study DEP (0, 0.25, 2.5, and 5%) or DMP (0, 0.25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…BMS-2 is not a selective developmental toxicant in the rat, but at doses greater than or equal to 10 times the maternal LOAEL, it produced reduced fetal body weights, resorptions, fetal edema, encephalocele, and malformations of the abdomen and tail. Dimethyl phthalate is a short chain phalatic acid ester that has been found to be non-teratogenic in mammalian studies (Plasterer et al, 1985;Field et al, 1993). However, zebrafish embryos treated with dimethyl phthalate developed a low incidence of general dysmorphology at 1 Â 10 À5 or 1 Â 10 À4 M that appeared to be compoundrelated.…”
Section: Discussionmentioning
confidence: 94%
“…BMS-2 is not a selective developmental toxicant in the rat, but at doses greater than or equal to 10 times the maternal LOAEL, it produced reduced fetal body weights, resorptions, fetal edema, encephalocele, and malformations of the abdomen and tail. Dimethyl phthalate is a short chain phalatic acid ester that has been found to be non-teratogenic in mammalian studies (Plasterer et al, 1985;Field et al, 1993). However, zebrafish embryos treated with dimethyl phthalate developed a low incidence of general dysmorphology at 1 Â 10 À5 or 1 Â 10 À4 M that appeared to be compoundrelated.…”
Section: Discussionmentioning
confidence: 94%
“…An increased incidence of fetuses with skeletal defects was observed in rats administered DEP (0.338-1.125 mL/kg) by intraperitoneal injections on days 5, 10 and 15 of gestation (Singh et al, 1972). It is also reported that supernumerary ribs (a skeletal vari-ation) in fetuses was induced following dietary administration to maternal rats on days 6 through 15 of gestation at a dose level of 5% DEP (Field et al, 1993). No maternal or developmental toxicity was found after oral administration of DEP to the dam at 750 mg/kg from gestation day 14 to postnatal day 3 (Gray et al, 2000).…”
Section: Introductionmentioning
confidence: 94%
“…Numerous animal studies have reported adverse effects of BPA at doses below the current RfD of 50 μg/kg per day on a range of phenotypes, including metabolic processes such as pancreatic function and insulin and glucose homeostasis. [89][90][91][92][93] Some report that pre-and postnatal developmental exposure to low doses of BPA and phthalates stimulates weight gain, [94][95][96][97][98][99] and has catabolic effects at high levels. 100,101 These studies and those discussed below suggest that these chemicals may increase the risk of T2D by affecting multiple biological pathways that are of critical importance in T2D development.…”
Section: Endocrine-disrupting Effects Of Bpa and Phthalate Exposure Imentioning
confidence: 99%